ANALISIS STRUKTUR MODAL DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT FKS FOOD SEJAHTERA TBK PERIODE TAHUN 2013 - 2022 - Zanuba, Iqrima Apik; Mardiana, Sri (Journal of Research and Publication Innovation, 2024)
This study is to determine the Financial Performance of PT FKS Food Sejahtera Tbk for the Period 2013-2022 in terms of Capital Structure and Profitability. This type of research uses descriptive analysis methods with a quantitative approach. Based on the research results, the Capital Structure calculated using the Solvency Ratio, namely the Debt to Asset Ratio obtained an average value of 113.18% declared